Interlinking the Arab Gulf: Opportunities and Challenges of GCC Electricity Market Cooperation - El-Katiri, L (Oxford Institute for Energy Studies, 2011)
The GCC countries have experienced tremendous economic growth over the past decade as a result of high windfall revenues from their oil and natural gas exports. At the same time, the region’s own energy consumption, including of electricity, has risen fast, leading to various capacity bottlenecks in the short term with recurrent electricity outages along the Gulf coast for consecutive summers at times of peak demand. In this context, it has been noteworthy that one of the GCC’s most recent mega-project, the GCC Interconnection Grid, went online in July 2009 with its first phase. The GCC Grid is aimed at enabling the opening of a regional market for electricity, with various potential benefits for GCC electricity supply security, as well as economic benefits. In this paper, Laura El-Katiri tried answering the question to what extent intra-GCC electricity trading could potentially be part of a mid- to long term solution for the GCC states in increasing their electricity sectors’ supply security as well as their market efficiency. She concludes that potential for commercial trade in electricity between the GCC states does exist, but various features of national electricity markets in the GCC mean this potential is likely to materialise only in the long term. Until then, the GCC Grid stays an expensive but strategically useful piece of infrastructure which may one day form the backbone of a more integrated, regional market.